Sustainability in Fashion : A Critical Discourse Analysis of Ecological Sustainability Claims on the Websites of Three Clothing Brands - Holma, Lilli (My University, 2025)
This thesis examines the sustainability sections of the websites of three clothing companies: Shein, H&M and Dior. It focuses on the sustainability claims these companies make in order to share information regarding their sustainability. Critical Discourse Analysis is employed with the aim to investigate how each company uses language to convey their ecological sustainability values and efforts. The analysis also considers the possible intentions behind the sustainability communication and compares the different strategies the companies use. Both writing and images are analyzed through the lens of Multimodal Discourse Analysis. In addition, the thesis draws on ecolinguistics and aspects of van Leeuwen’s Social Actor Analysis. This thesis provides an overview of the sustainability communication the brands use on their websites, particularly in the sections created specifically to inform customers about their sustainability initiatives. A common trait of all the sustainability sections is the vague language used while not much concrete evidence of environmentally friendly practices is given. This is an indicator of greenwashing and aligns with previous research. Overall, the sustainability sections analyzed, images and writing included, can be described as ambivalent discourses. Several interesting follow-up studies could explore this topic in more detail, for example from the perspective of consumer perceptions.
Keywords: sustainability, fashion, greenwashing, critical discourse analysis